Self-compacting mortars with mineral additions: Perlite and limestone filler - Artigas, Verónica Fernanda (2021)
With the increasing infrastructure and the need for eco-sustainable alternatives, the concrete industry has motivated to look for supplementary cementitious materials especially those generated from waste. The advantages of self-compacting concrete (SCC) make it useful in the worldwide; therefore, it is essential to study additions that can be incorporated into it, to improve its properties. Limestone powder (LP) and local waste perlite fines (PF) from Salta (Argentina) are proposed as mineral addition in self-compacting mortars (SCM). PF has a high content of SiO2 and Al2O3 which can contribute to increasing the strength of the concrete due to the pozzolanic reaction. Physicochemical characterization of this waste is studied and the behavior of SCM mixtures with different proportions of LP and PF are also analyzed. Sets of specimens have been performed in order to test their rheological characteristics in the fresh state and their mechanical resistance in the hardened state. The results indicate that the combination of LP and PF has a beneficial influence on the fresh state, granting an adequate fluidity and viscosity of the mixture; on the hardened state, compressive strengths similar to the standard are achieved at 90 days in mortars with up to 20% cement replacement by additions.